Colonization of Lutzomyia verrucarum and Lutzomyia longipalpis Sand Flies (Diptera: Psychodidae) by Bartonella bacilliformis, the Etiologic Agent of Carrión's Disease. - James M Battisti; Phillip G Lawyer; Michael F Minnick (Public Library of Science (PLoS), 2015)
Bartonella bacilliformis is a pathogenic bacterium transmitted to humans presumably by bites of phlebotomine sand flies, infection with which results in a bi-phasic syndrome termed Carrión's disease. After constructing a low-passage GFP-labeled strain of B. bacilliformis, we artificially infected Lutzomyia verrucarum and L. longipalpis populations, and subsequently monitored colonization of sand flies by fluorescence microscopy. Initially, colonization of the two fly species was indistinguishable, with bacteria exhibiting a high degree of motility, yet still confined to the abdominal midgut. After 48 h, B. bacilliformis transitioned from bacillus-shape to a non-motile, small coccoid form and appeared to be digested along with the blood meal in both fly species. Differences in colonization patterns became evident at 72 h when B. bacilliformis was observed at relatively high density outside the peritrophic membrane in the lumen of the midgut in L. verrucarum, but colonization of L. longipalpis was limited to the blood meal within the intra-peritrophic space of the abdominal midgut, and the majority of bacteria were digested along with the blood meal by day 7. The viability of B. bacilliformis in L. longipalpis was assessed by artificially infecting, homogenizing, and plating for determination of colony-forming units in individual flies over a 13-d time course. Bacteria remained viable at relatively high density for approximately seven days, suggesting that L. longipalpis could potentially serve as a vector. The capacity of L. longipalpis to transmit viable B. bacilliformis from infected to uninfected meals was analyzed via interrupted feeds. No viable bacteria were retrieved from uninfected blood meals in these experiments. This study provides significant information toward understanding colonization of sand flies by B. bacilliformis and also demonstrates the utility of L. longipalpis as a user-friendly, live-vector model system for studying this severely neglected tropical disease.